Evaluation Of Side Effects Of First-Line Antiretroviral (ARV) Therapy In HIV Patients At Kassi-Kassi Public Health Center Of Makassar - Dwi Rantisari Thayeb, Andi Meinar; Kesrianti, A. Maya; Saputri, Rizky; Saleh, Adriandy (Sean Institute, 2024)
The treatment for HIV/AIDS therapy is by administering antiretrovirals (ARVs) for life, therefore it is necessary to monitor patients for side effects or symptoms of ARV toxicity. The aim of this study is to evaluate the side effects of drugs in HIV sufferers who were taking first-line antiretroviral (ARV) drugs at the Kassi-Kassi Public Health Centre of Makassar. This research was quantitative research with descriptive research type. The results showed that of the 36 patients who met the inclusion and exclusion criteria based on their characteristics, the majority of respondents were male (91.67%), in the 25-54 year age group (72.22%), and had a tertiary level education ( 58.33%). Based on the length of time they received antiretroviral drug therapy (ARV), the majority of patients were in the 6 months-5 years category (80.56%), with the most widely used ARV combination being tenofovir + lamivudine + efavirenz (47.22%). The number of patients who did not experience ARV side effects was greater (50.7%) than those who experienced side effects. The most common side effects include:dizziness, nausea, rash, fatigue and sleep disturbances. Even though several patients experienced ARV side effects, judging from the medical records, after treatment of ARV side effects, the patients continued therapy well.